Advances in pharmacotherapy for postpartum depression: a structured review of standard-of-care antidepressants and novel neuroactive steroid antidepressants - Yardana Kaufman; Sara V. Carlini; Kristina M. Deligiannidis (SAGE Publishing, 2022)
Postpartum depression is one of the most common morbidities of childbearing, yet it is underdiagnosed and undertreated with negative consequences for mother and offspring. Despite the widespread use of standard-of-care antidepressants as the mainstay of treatment for postpartum depression, there is limited evidence on their safety and efficacy due to their slow onset of action and suboptimal outcomes. The emergence of gamma-aminobutyric acidergic neuroactive steroids may offer faster response and remission times and improved patient outcomes. This article reviews the evidence base for the efficacy of standard-of-care antidepressants, hormonal therapeutics including progestins and estradiol, and gamma-aminobutyric acidergic neuroactive steroids in the treatment of postpartum depression, as well as the safety of infant exposure to these agents during lactation.